Pembentukan Karakter Siswa Ditinjau dari Spiritualitas Perkumpulan Dharmaputri dan Dukungan Orang Tua - Monica Innanda Chiaralazzo; Paskalis Edwin I Nyoman Paska; Laurensius Laka (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
Education within the Catholic Church has always had its distinct characteristics. The unique characteristics of Catholic schools are implemented at SMAK Santa Maria Malang. In addition to the school, parents also play a role in shaping the character of students. However, not all students at SMAK Santa Maria Malang exhibit good character, especially in terms of respect and responsibility. This study aims to determine the influence of Dharmaputri spirituality and parental support on the character formation of students at SMAK Santa Maria Malang. To achieve the research objectives, multiple linear regression analysis was used with the help of SPSS for Windows 26. The population in this study consisted of 403 students, with a sample size of 200 students. The sampling technique employed was random sampling. The findings revealed a correlation coefficient (R) of 0.905, indicating a positive correlation between the two variables with a very strong relationship. Furthermore, the Dharmaputri Spirituality variable obtained a t-value (0.000<0.05), and the Parental Support variable also obtained a t-value (0.000<0.05), meaning that both variables independently have a significant influence on character formation. Based on the SPSS output table, the significant F-value was obtained (0.000<0.05), indicating that there is an influence between Dharmaputri Spirituality and Parental Support on Character Formation simultaneously. Thus, Dharmaputri spirituality and parental support together have an impact on the character formation variable.